Potensi Babi Sebagai Sumber Penularan Penyakit Zoonosis Entamoeba spp - Suryawan, Gede Yudi; Suratma, Nyoman Adi; Damriyasa, I Made (Buletin Veteriner Udayana, 2014)
Pig is not only a source of protein and has a socio-cultural values, but also a potential source of some zoonotic disease. Entamoeba spp is a common zoonotic disease that are transferred by the pig. The aim of study is to determine the potential source of pig to transferred the zoonotic disease expecialy Entamoeba spp for human. One hundred seventy three feces samples of humans and 102 feces samples of pigs were collected in SAF solution. The prevalence of Entamoeba spp infections in human and pig were presented and analyzed statistic by using spearman correlation. The result of the study showed that the prevalence of Entamoeba spp in pig and human 32,4 % and 21,92% , it was the significant correlation (P<0,05) between the prevalence of Entamoeba spp infection in pig and human.
Keywords: Entamoeba spp, pigs, potential, zoonoses